'The unbearable surplus of being human': Happiness, virtues and the delegitimisation of the negative. Issue 4 (21st October 2022) - Hodgson, Naomi
Abstract: The increased governmental focus on happiness since the late 1990s, and particularly since the economic crash of 2008, has been informed predominantly by a conceptualisation of happiness promoted by the field of positive psychology, and adopted and developed in fields such as behavioural economics and more recently in fields such as neuroeducation. Concepts, or traits, associated with feeling happy or satisfied with our lives, such as resilience, are now promoted across both public and private domains as a means to improve our quality of life, our productivity and our attainment. The promotion of this positive psychological notion of happiness in the context of education not only presents these traits as virtues of the productive learning citizen but also effects a delegitimisation of the negative. Analysis of curricula programmes, seen alongside the shift taken towards a focus on the individual as brain, highlights the pedagogical and political implications of this.